2018
DOI: 10.1002/hbm.24284
|View full text |Cite
|
Sign up to set email alerts
|

The consequence of cerebral small vessel disease: Linking brain atrophy to motor impairment in the elderly

Abstract: In the elderly, brain structural deficits and gait disturbances due to cerebral small vessel disease (CSVD) have been well demonstrated. The relationships among CSVD, brain atrophy, and motor impairment, however, are far from conclusive. Particularly, the effect of CSVD on subcortical nuclear atrophy, motor performance of upper extremities, and associating patterns between brain atrophy and motor impairment remains largely unknown. To address these gaps, this study recruited 770 community-dwelling subjects (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…Compared to HCs, both of the WMH groups exhibited volumetric loss of deep subcortical GM nuclei, especially the bilateral thalamus, in line with previous studies focused on subcortical vascular MCI patients [12] or patients with high WMH load from a community-dwelling cohort [43]. Furthermore, to extend their findings, we found that the WMH-MCI patients showed a more widespread and severe reduction of thalamic GMV than the WMH-nCI patients and further identified positive correlations between several subregions of the thalamus and cognition (processing speed and executive function) within the WMH-MCI group.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to HCs, both of the WMH groups exhibited volumetric loss of deep subcortical GM nuclei, especially the bilateral thalamus, in line with previous studies focused on subcortical vascular MCI patients [12] or patients with high WMH load from a community-dwelling cohort [43]. Furthermore, to extend their findings, we found that the WMH-MCI patients showed a more widespread and severe reduction of thalamic GMV than the WMH-nCI patients and further identified positive correlations between several subregions of the thalamus and cognition (processing speed and executive function) within the WMH-MCI group.…”
Section: Discussionsupporting
confidence: 89%
“…Motor performance was quantified using standard motor scales, which have been described elsewhere 26 , 40 . The lower-extremity function was evaluated via 3-m walking speed and 5-repeat chair-stand time.…”
Section: Methodsmentioning
confidence: 99%
“…However, subcortical syndromes, such as gait disorders, tend to be neglected because of their insidious onset. Certainly, not all individuals with CSVD eventually experience gait disturbances, although CSVD has been recognized as a possible cause of gait impairment (Su et al, 2018 ). In other words, the motor impairments associated with CSVD cannot be fully interpreted by WMHs or LAs on MRI.…”
Section: Introductionmentioning
confidence: 99%